The restaurant at the end of the universe [compact disc, unabridged] - Adams, Douglas, 1952-2001 (Adams, Douglas, 1952-2001. Hitchhiker's guide to the galaxy., 2006)
Arthur Dent, a refugee from the late planet Earth and his pal from the planet Betelgeuse, Ford Prefect, thumb their way thru comic misadventures throughout the Universe. In this installment Dent now seeks a decent cup of tea, while Prefect is after a good gin and tonic.